2005
DOI: 10.1248/cpb.53.974
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pore Size of FSM-16 on the Entrapment of Flurbiprofen in Mesoporous Structures

Abstract: The improvement of bioavailability of poorly water-soluble drugs is important for oral administration. Amorphization is one of the techniques that has been commonly used for solubility enhancement.1,2) Amorphous material of drug can be obtained by several methods, e.g., spray-drying, 3) solid dispersion, 4) co-grinding with cyclodextrins 5) or crystalline cellulose, 6) and mixing with porous materials. 7,8) Porous materials have a unique capacity to adsorb organic compounds due to their large specific surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…[8][9][10] The large pore volume allows high drug loading into the ordered matrix. The large surface area of the internal surface can be modified according to specific purposes for different drugs association on the surface of matrix.…”
mentioning
confidence: 99%
“…[8][9][10] The large pore volume allows high drug loading into the ordered matrix. The large surface area of the internal surface can be modified according to specific purposes for different drugs association on the surface of matrix.…”
mentioning
confidence: 99%
“…The decrease in the mean pore width was considered to be a result of the shrinkage of FSM mesopores due to the formation of hydrogen bonds between flurbiprofen and FSM in the solid dispersions. The existence of adsorbed flurbiprofen layers was proposed from the decrease in the specific surface area and pore volume of mesoporous silica (Tozuka et al, 2005). Our findings from nitrogen sorption isotherms suggested that insulin molecules were entrapped in the mesopores of FSMs after the samples were freeze-thawed 10 times.…”
Section: Untreatedmentioning
confidence: 64%
“…Recently, other MSN porous structures, including the spherical structures, the hierarchically porous structures, and single-crystal structures, were produced by different methods, e.g. sol-gel [9,10], microemulsion [11,12], and template [13,14]. The porous nature of the MSNs allows them to be loaded with different types of molecules.…”
Section: Introductionmentioning
confidence: 99%